Elevated Carcinoembryonic Antigen at the Time of Recurrence as a Poor Prognostic Factor in Colorectal Cancer: A Propensity Score Matching Analysis - Shin, Jung Kyong; Huh, Jung Wook; Lee, Woo Yong; Yun, Seong Hyeon; Kim, Hee Cheol; Cho, Yong Beom; Park, Yoon Ah (Frontiers in Oncology, 2022)
The prognostic impact of CEA level at the time of recurrence in recurrent colorectal cancer has not been addressed. The objective of this study was to evaluate the prognostic value of serum CEA levels at the time of recurrence in patients with recurrent colorectal cancer. Between 2007 and 2014, 962 consecutive recurrent patients for colorectal cancer were analyzed. These patients were classified into two groups according to CEA level at the time of recurrence (r-CEA): high r-CEA (≥ 5 ng/ml) (n = 428) and normal r-CEA (< 5 ng/ml) (n = 534). We used 1:1 propensity score matching (PSM) to adjust for potential baseline confounders between groups. A total of 778 patients were matched, with 389 in each group. Patients with an elevated r-CEA level showed significantly poorer survival than those with normal levels. The 5-year overall survival rate was 56.5% in the high r-CEA group and 66.0% in the normal r-CEA group (p = 0.008). The 5-year cancer specific survival rate was 61.7% in the high group and 67.5% in the normal group (p = 0.035). In multivariate analysis of prognostic factors, high preoperative CEA level at the time of recurrence, poor histologic grade and lymphatic invasion were associated with poorer overall survival. Patients with colorectal cancer who have an elevated r-CEA level show significantly poorer prognosis than those with normal levels of r-CEA. Therefore, r-CEA level can be used as an additional prognostic indicator of poor outcomes in colorectal cancer. Aggressive adjuvant treatment needs to be considered for patients with initially high CEA level and lymph node positive who are prone to recurrence.